“Cognitive Thinking, Fifth Scientific Grade, Badioudi, Earth Science” (Journal of the College of Basic Education, 2026)
This study aims to identify the effectiveness of the Pdeode strategy in developing metacognitive thinking skills among fifth-grade science students in the Earth Science subject. To achieve the study's goal, the researchers followed the experimental method, choosing a partially controlled experimental design. This is a randomized design with pre- and post-tests, with an experimental and control group. The two researchers intentionally chose a sample of (60) female students. The researcher rewarded the two research groups in several variables and adopted the metacognitive thinking skills scale of (Shro and Denison 1994). The results of the study yielded the following: • There are statistically significant differences at the level of (0.05) between the average scores of the students of the experimental group and the control group in the post-metacognitive thinking skills scale in the three areas (knowledge of knowledge, organization of knowledge, knowledge processing) in favor of the students of the experimental group